2018
DOI: 10.1177/0886260518766420
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Factors Associated With Prosocial Skills and Maladaptive Functioning in Youth Exposed to Intimate Partner Violence

Abstract: Children are frequently present in homes in which intimate partner violence (IPV) occurs. Following exposure to IPV, children may develop behavioral health difficulties, struggle with regulating emotions, or exhibit aggression. Despite the negative outcomes associated with witnessing IPV, many children also display resilience. Guided by Bronfenbrenner's bioecological model, this study examined person-level, process-level (microsystem), and context-level (mesosystem) factors associated with positive and negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 60 publications
3
21
1
1
Order By: Relevance
“…Our findings are not consistent with a large number of previous findings that suggest prosocial skills are a protective factor against child externalizing behaviour (Carlson et al 2019;Howell et al, 2021;Oravecz et al, 2011, Garrido & Taussig, 2013. One study by Goelman et al (2014) found that children exposed to maternal depression and low-quality childcare exhibited more behavioural problems and worse prosocial functioning.…”
Section: Child Prosocial Skillscontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings are not consistent with a large number of previous findings that suggest prosocial skills are a protective factor against child externalizing behaviour (Carlson et al 2019;Howell et al, 2021;Oravecz et al, 2011, Garrido & Taussig, 2013. One study by Goelman et al (2014) found that children exposed to maternal depression and low-quality childcare exhibited more behavioural problems and worse prosocial functioning.…”
Section: Child Prosocial Skillscontrasting
confidence: 99%
“…Child prosocial skills is another factor that has been consistently identified in the IPA and child conduct literature as an important mechanism between these two variables (Holmes et al, 2015;Oravecz et al, 201;Camacho et al, 2012;Garrido & Taussig, 2013;Howell et al, 2021;Goelman et al, 2014). For example, Holmes et al (2015) investigated the impact of IPA on child aggressive behaviour and prosocial skills across two time points.…”
Section: The Role Of Child Prosocial Skillsmentioning
confidence: 99%
“…Comportamentalmente se reconocieron la: mediación, la solución de conflictos, la comunicación (Bain & Durbach, 2018), el establecimiento de límites, las relaciones interpersonales positivas, la búsqueda de información y el apoyo por parte de la policía (Cherewick et al, 2015) la ayuda a otros, la solidaridad y el empoderamiento (Fellin et al, 2019;Goodman, et al, 2016), el emprendimiento (Green, Blattman, Jamison, & Annan, 2015), la generación de redes de apoyo (Gregory, Williamson, & Feder, 2017) y el desarrollo de habilidades prosociales (Howell, Thurston, Hasselle, Decker, & Jamison, 2018).…”
Section: Total 74unclassified
“…Explorations of the etiology of CD and APD have included a focus on the potentially deleterious effects of children's exposure to IPV (Howell, Thurston, Hasselle, Decker, & Jamison, ; Kimber et al, ; Vu, Jouriles, McDonald, & Rosenfield, ), but less often on exposure to AA, especially AA perpetrated by a caregiver. Ascione et al () found that 67% of children whose mothers were IPV survivors reported that they had seen or heard pet animal abuse.…”
Section: Aa and Crimementioning
confidence: 99%